2015
DOI: 10.1016/j.neuroscience.2015.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Protracted abstinence from chronic ethanol exposure alters the structure of neurons and expression of oligodendrocytes and myelin in the medial prefrontal cortex

Abstract: In rodents, chronic intermittent ethanol vapor exposure (CIE) produces alcohol dependence, alters the structure and activity of pyramidal neurons and decreases the number of oligodendroglial progenitors in the medial prefrontal cortex (mPFC). In this study, adult Wistar rats were exposed to seven weeks of CIE and were withdrawn from CIE for 21 days (protracted abstinence; PA) and tissue enriched in the mPFC was processed for Western blot analysis and Golgi-Cox staining to investigate the long-lasting effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 86 publications
(110 reference statements)
4
32
0
Order By: Relevance
“…Importantly, these changes were also associated with deficits in cognitive flexibility, which lasted up to one week into abstinence. A subsequent study examining expression of GluN2B-containing NMDA receptors in the mPFC following three weeks of abstinence from chronic intermittent ethanol vapor exposure reported similar findings with unaltered total GluN2B levels despite the presence of significantly increased dendritic arborization of pyramidal neuron apical dendrites within this region (Navarro and Mandyam, 2015). Interestingly, while total GluN2B levels were unchanged at this time-point, the authors reported a significant reduction in the levels of phosphorylated GluN2B-containing receptors.…”
Section: Glutamatergic Adaptations Involved In Dependence-induced mentioning
confidence: 77%
“…Importantly, these changes were also associated with deficits in cognitive flexibility, which lasted up to one week into abstinence. A subsequent study examining expression of GluN2B-containing NMDA receptors in the mPFC following three weeks of abstinence from chronic intermittent ethanol vapor exposure reported similar findings with unaltered total GluN2B levels despite the presence of significantly increased dendritic arborization of pyramidal neuron apical dendrites within this region (Navarro and Mandyam, 2015). Interestingly, while total GluN2B levels were unchanged at this time-point, the authors reported a significant reduction in the levels of phosphorylated GluN2B-containing receptors.…”
Section: Glutamatergic Adaptations Involved In Dependence-induced mentioning
confidence: 77%
“…These results suggest that mPFC, in part via GR signaling, can modulate the mesocorticolimbic pathway and thereby regulate anxiety-like and aggression-like negative affect symptoms (Butts and Phillips, 2013; Miczek et al, 2015b). Previous research shows that acute withdrawal (2-10 h) from ethanol in CIE rats altered structural neuroplasticity in the mPFC pyramidal neurons (Kim et al, 2014) and decreased expression of GR mRNA in the mPFC without altering GR protein expression and signaling, among other regions (Navarro and Mandyam, 2015; Vendruscolo et al, 2012). Further, these studies do not reveal whether these changes persist into extended ethanol abstinence (24 h and longer).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly interesting is the long-lasting effect of withdrawal on OPCs in the mPFC, visualized as increases in proliferation and survival of progenitors in CIE-ED animals that also demonstrated enhanced drinking after prolonged abstinence, suggesting a permanent dysregulation in the oligodendroglial niche maintaining oligodendroglial homeostasis (Somkuwar et al, 2015). Protracted abstinence from CIE is also associated with increases in myelin associated proteins in the mPFC indicating additional compensatory changes in myelinating glia (Navarro and Mandyam, 2015). Such alterations in the expression of oligodendroglia and myelinating glia during withdrawal and abstinence in the mPFC may be regulated by neuroinflammatory response during withdrawal, as interactions between oligodendroglia, myelin, endothelial cells and neuroinflammatory proteins have been demonstrated in models of brain injury, including, stroke and ischemia (Pham et al, 2012, Ortega et al, 2015).…”
Section: 0 Introductionmentioning
confidence: 99%